(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1869)
A gold brooch was displayed at the meeting. Although the author was unable to provide much any information about it, he was able to give an account of where it was found. Based on its design, he suggests that it may have been made some time in the thirteenth to sixteenth centuries, possibly for a member of the nobility visiting Doune Castle.